Teachers' Metaphorical Perceptions About School Principals' Humor Styles - Damla Ayduğ; Beyza Himmetoğlu; Coşkun Bayrak (Anı Publishing, 2018)
The main aim of this study is to determine teachers' perceptions about school principals' humor styles through metaphors. The study, which is the qualitative research, was designed as a basic qualitative research. The working group of the study was consisted of 73 teachers working at public schools in Eskisehir during 2015-2016 academic year. In order to determine teachers' perceptions about school principals' humor styles, the form, written the following sentence: "school principal's humor style is like ........, because it is ........" was given to the participants and it was requested to fill this form from participants. Data obtained has been analyzed by using content analysis. Findings of the study showed that 60 teachers produced 53 valid about the concept of school principals' humor styles and these metaphors were grouped under 8 different categories. There categories are; motivator humor, problem-solving humor, sarcastic humor, changeable humor, nonhumor style, balanced humor, thought-provoking humor and reflective humor. According to the results of the study, it was determined teachers produced more metaphors about motivator humor and problem-solving humor styles compared with other styles. Teachers produced less metaphors about reflective humor style.